Integrated approach of nutritional and molecular epidemiology, mineralogical and chemical pollutant characterisation: the protocol of a cross-sectional study in women. Issue 4 (4th April 2017) - Barchitta, Martina; Quattrocchi, Annalisa; Maugeri, Andrea; Barone, Germana; Mazzoleni, Paolo; Catalfo, Alfio; De Guidi, Guido; Iemmolo, Maria; Crimi, Nunzio; Agodi, Antonella
Abstract : Introduction: Environmentally-related health and disease are the result of the exposome, the totality of a person's environmental exposures, from all sources and routes, across their lifespan. Epigenetic phenomena, including DNA methylation, can be potentially modified by environmental and lifestyle factors, and result in environmental reprogramming of the genome for exposed individuals and for future generations of offspring. Objective: The objective of the project is to evaluate the risk of DNA hypomethylation due to air pollution, Mediterranean diet adherence, folate intake, and demographic and socioeconomic factors, in healthy women living in the metropolitan area of Catania, Italy. Methods and analysis: Non-pregnant healthy women will be enrolled in a cross-sectional study. Sociodemographic, lifestyle and dietary intake information will be collected. LINE-1 methylation will be measured by pyrosequencing. The participants' home addresses will be geocoded and each woman will be assigned to the closest monitoring station for particulate matter (PM) exposure assessment. Mineralogical-chemical characterisation of PM and cellular model assays will be performed. An integrated approach will be designed to estimate the combined possible effect of air pollution, Mediterranean diet adherence, folate intake and other lifestyle characteristics on LINE-1 methylation levels. Ethics and dissemination: The project has been approved by the ethics committees of the involved institution and funded by the University of Catania (Finanziamento della Ricerca, FIR 2014). All participants will be fully informed of the purpose and procedures of the study, and signed written consents will be obtained. All the data collected will be treated confidentially and analysed in an aggregate and anonymous way. The results will be published in peer-reviewed journals and communicated to local public health agencies, in order to provide essential information for timely and effective public health action.